(untitled) (Comparatismi, 2017)
The original idea of intersemiotic translation created by Roman Jakobson, which implies the translation of one sign system to another, has been specially associated with book-to-film translation and vice-versa, amongst many other possibilities. Within this conception, it has been commonly considered the whole text as well as the fully translated version into another system. However, there is a text type in which several sign systems are constantly interplaying, where the translation into another language or culture would require the consideration of all intersemiotic possibilities so as to “better convey” its meanings to the target readers: we are referring to comics. This work aims to reflect upon the kind of intersemiotic translation that occurs in a comic album that is translated from one language into another, i.e., as understood by Jakobson’s classification as interlingual translation. To develop this idea, some pairs of frames (from French into Brazilian Portuguese) from comic books of the French character Asterix were analysed, seeking to show how the translator handled the comics’ several possible communication modes (words, typography, object images, human expressions and gestures, layouts). From this analysis it was observed that the translator can use one mode (here the multimodality concept is evoked) to translate another, thus surpassing barriers usually established to keep comics images from being altered (due to copyright or any other reasons). In fact, the translator uses different modes of translation, often “retrieving” meanings from other modes—although not always successfully—, but showing great creativity most of the time. Going back to Jakobson’s idea, this work also intends to show that intersemiotic translation is embedded in the other two types of translations suggested by this renowned linguist. Consequently, such classification (intralingual, interlingual, intersemiotic) can be subject to questioning and further development.